(3CMeO Thbj (B:s (3TGYQ GdhWfjI hGdeSQM hGdJGQjN (B/s - (3YWhj, ahRj,s 1939-2008 ((3dHfGf (B- (3HjQhJs (3OGQ GdacQ GdYQHj ,s, 1989)
(3jJMOK gPG GdcJGH Yf MjGI GdTGYQ CMeO Thbj hYf NUGFU TYQg hCSdhHg, hgh TGYQ GdhWfjI hGdeSQM hGdJGQjN hbO dbH HCejQ GdTYQGA(B.s
(3HHdjhLQGajI (B: (3UaMI (B89.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3CMeO Thbj,s -- 1868-1932; (3GdTYQGA GdYQHs -- (3JQGLes